2017
DOI: 10.1016/j.neubiorev.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning and chronic methadone use: A systematic review and meta-analysis

Abstract: Methodological issues such as small sample sizes, heterogeneity and poor quality limited the interpretation of the results and does not address whether the observed impairments reflect co-morbid functioning, methadone-related sedation and/or other factors. Only higher quality longitudinal studies will permit confident interpretation of the results observed in this meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 58 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…The neurotoxic effects of opioids, cognitive deficits due to opioids, and possible remission of symptoms are a matter of debate [2,4,25,[43][44][45]. Previous studies in former opioid users showed a poorer performance than controls on some tasks, but most findings were without clinical relevance (e.g., [8]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurotoxic effects of opioids, cognitive deficits due to opioids, and possible remission of symptoms are a matter of debate [2,4,25,[43][44][45]. Previous studies in former opioid users showed a poorer performance than controls on some tasks, but most findings were without clinical relevance (e.g., [8]).…”
Section: Discussionmentioning
confidence: 99%
“…Schulte et al [1] concluded that sustained abstinence in people with substance use disorders generally results in (partial) neurocognitive recovery. Only limited data are available regarding cognitive functioning in opioid-dependent people so far (for recent reviews see [2][3][4][5]) and just a small amount of research has dealt with cognitive functioning in formerly opioid-dependent people [4,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The impairments of neurocognitive functions in patients with opioid dependence were consistent with the evidence in the literature. [1][2][3] Both the meta-analyses by Baldacchino and colleagues and Wollman et al done on patients using heroin (and other illicit opioids) and on patients undergoing methadone treatment revealed a global cognitive dysfunction in the domains of attention, cognitive impulsivity, decision making, psychomotor speed, and memory. The effect sizes estimated in these meta-analyses ranged from 0.11 (for attentional impairment) to 0.70 and 0.97 (for impairment in cognitive impulsivity and complex psychomotor function).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent meta-analysis by Wollman and colleagues showed small to medium effect sizes for dysfunctions in attention, working memory, and executive function. 2 Another metaanalysis in individuals on methadone maintenance showed comparable cognitive impairment. 3 These reviews would unequivocally suggest an association of chronic opioid use (both illicit and used as treatment) and neurocognitive impairment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation